2008
DOI: 10.1021/jm800101w
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)-Mediated Inhibition of Protein Tyrosine Phosphatases: A Detailed in Vitro and Cellular Study

Abstract: Gold(I) complexes containing N-heterocyclic carbene ligands were synthesized, characterized, and along with the antiarthritic drug, auranofin, tested as inhibitors of the cysteine-dependent protein tyrosine phosphatases, which are implicated in several disease states. These compounds exhibit potencies in the low micromolar range against the enzymes in vitro. At therapeutically relevant concentrations, all compounds inhibit PTP activity in Jurkat T leukemia cells with some selectivity. In addition, the gold-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
111
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 31 publications
5
111
0
Order By: Relevance
“…Thus, our findings collectively lead to the conclusion that auranofin in the present study affects PDGFβR phosphorylation through inhibitory effects on TrxR1, rather than by direct effects on PTP1B. It should be noted, however, that other PTPs such as PTPN12 seem to be more sensitive to direct inhibition by auranofin (57).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, our findings collectively lead to the conclusion that auranofin in the present study affects PDGFβR phosphorylation through inhibitory effects on TrxR1, rather than by direct effects on PTP1B. It should be noted, however, that other PTPs such as PTPN12 seem to be more sensitive to direct inhibition by auranofin (57).…”
Section: Discussionsupporting
confidence: 77%
“…On the basis of the inactivation of PTP1B in Txnrd1 −/− cells, the stimulatory effects of auranofin on PDGFβR phosphorylation are interpreted to be a consequence of effects of auranofin on TrxR1 (56). It should be noted that auranofin has also been shown to act as a direct PTP inhibitor (57). However, direct inhibition of PTP1B by auranofin was inefficient and showed an IC 50 of >400 μM (57), whereas auranofin inhibits TrxR1 at stoichiometric submicromolar concentrations (56).…”
Section: Discussionmentioning
confidence: 99%
“…Mercuric ion reductase, a related NADPHdependent oxidoreductase, also is known to bind mercuric ion in a similar fashion (44). In addition, given the thiophilic nature of the compound, it is possible that auranofin may react with other enzymes bearing reactive cysteine residues, such as cysteine proteases and phosphatases (45,46). Indeed, we found that auranofin can inhibit M. tuberculosis mycothione reductase in vitro, albeit with greatly reduced potency relative to its inhibition of TrxB2 (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The structures of vanadium complexes influence the inhibition over different PTPs Gao et al 2009;Lu et al 2010). Recent researches reveal other metal complexes such as Au, Cu, Fe complexes are also potent PTP inhibitors Gomez et al 2010;Karver et al 2009: Krishnamurthy et al 2008). Barrios' researches show gold complex auranofin potently and selectively inhibit PTP-PEST with IC 50 of 9 lM over HePTP, CD45, TCPTP, YopH, PTP1B and LYP, while complexes [(p-MeBzMeIm)Au I Cl] and [(BzMeIm)Au I Cl] potently inhibit PTP-PEST, HePTP, PTP1B and LYP with IC 50 from 7 to 40 lM.…”
Section: Introductionmentioning
confidence: 99%